Penerapan Model Problem Based Learning untuk Meningkatkan Proses dan Hasil Belajar Pendidikan Pancasila Kelas V di SD Negeri No.35/VI Seling - Mulki Zamzami; Abdulah Abdulah; Aldino Aldino (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study was conducted as a response to the issue of low student engagement and academic performance among fourth-grade students in the Pancasila Education subject at SD Negeri No. 35/VI Seling. The predominance of lecture-based instructional approaches has limited interactive dynamics in the classroom, thereby hindering students’ active participation in the learning process. The primary aim of this research is to enhance both instructional quality and student academic outcomes through the implementation of the Problem-Based Learning (PBL) model.The study employed a Classroom Action Research (CAR) design, implemented over two cycles, with each cycle consisting of two instructional sessions. The research subjects comprised 21 students. Data collection methods included structured observations of both teacher and student activities, as well as assessments to measure learning achievement. The instruments used in the study were observation checklists and evaluation test items.Findings from the study revealed a marked improvement in student participation and academic performance. Observation records indicated a rise in the teacher’s instructional effectiveness, progressing from the "good" category to "very good." Additionally, the percentage of students meeting the Minimum Mastery Criteria (KKTP) increased from 61.90% in the first cycle to 80.95% in the second cycle.Based on these findings, it can be concluded that the implementation of the PBL model is effective in elevating both the quality of the instructional process and student learning outcomes in Pancasila Education. Moreover, this approach holds considerable promise for broader application across various subjects to foster active engagement and the cultivation of critical and reflective thinking among students.